2002
DOI: 10.1095/biolreprod66.1.180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Type 3 and Type 4 Phosphodiesterase Inhibitors on the Maintenance of Bovine Oocytes in Meiotic Arrest1

Abstract: The use of broad-spectrum inhibitors first suggested that phosphodiesterases (PDEs) are involved in the maturation of bovine oocytes. Modulation of individual PDE families is now possible with the use of newly developed type-specific PDE inhibitors. This study evaluated the role of type 3- and type 4-specific PDE inhibitors on the meiotic arrest of bovine cumulus-oocyte complexes (COCs) and denuded oocytes (DOs). It also evaluated the role of these specific inhibitors on meiotic arrest when COCs are incubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 41 publications
5
74
1
1
Order By: Relevance
“…To date, several reports attest the efficiency of selective PDEIs to arrest oocyte meiosis when applied in a short culture period during follicle and oocyte development (Tsafriri et al 1996, Mayes & Sirard 2002, Thomas et al 2002, Jensen et al 2002, Nogueira et al 2003b). The present results have revealed that long-term exposure of germ cells and their somatic follicular cells to the PDE3 specific inhibitors, cilostamide or org9935, does not alter their normal development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several reports attest the efficiency of selective PDEIs to arrest oocyte meiosis when applied in a short culture period during follicle and oocyte development (Tsafriri et al 1996, Mayes & Sirard 2002, Thomas et al 2002, Jensen et al 2002, Nogueira et al 2003b). The present results have revealed that long-term exposure of germ cells and their somatic follicular cells to the PDE3 specific inhibitors, cilostamide or org9935, does not alter their normal development.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble forms of PDE3A exist in oocytes (Shitsukawa et al 2001), but the mechanisms of activation of the PDE3A remain unknown. Studies aiming to develop a new contraceptive strategy have shown that inhibition of PDE3A blocks oocyte meiosis in several species in vivo and in vitro (Tsafriri et al 1996, Wiersma et al 1998, Jensen et al 2002, Mayes & Sirard 2002, Nogueira et al 2003a.…”
Section: Introductionmentioning
confidence: 99%
“…Several years later, activity of the oocyte PDE3 was shown to increase before both spontaneous and gonadotrophin-induced meiotic resumption (Richard et al 2001). The effect of specific PDE3 inhibitors on maintaining oocyte meiotic arrest in vitro has now been demonstrated across many mammalian species: rats (Tsafriri et al 1996), mice (Wiersma et al 1998), cattle (Mayes & Sirard 2002, Thomas et al 2002, monkeys (Jensen et al 2002), humans (Nogueira et al 2003a) and swine (Laforest et al 2005). Demonstration of sterility of female mice bearing a PDE3A-null mutation due to the ovulation of GV-stage oocytes was the final proof of the central role of PDE3A in maintaining oocyte meiotic arrest (Masciarelli et al 2004).…”
Section: Cgmp and Phosphodiesterasesmentioning
confidence: 99%
“…In bovine oocytes, specific inhibition of PDE3 in vitro delayed spontaneous meiotic maturation and increased cAMP levels in cumulus cells and in denuded oocytes (BilodeauGoeseels, 2003b;Mayes & Sirard, 2002;Thomas et al, 2002). A study of PDE isoforms present in bovine follicle components showed that PDE3 accounted for 80% of the PDE activity in the oocyte, while PDE8 activity accounted for the remaining 20 and 60% of PDE activity in oocytes and cumulus cells, respectively.…”
Section: Role Of Phosphodiesterases In the Regulation Of Bovine Oocytmentioning
confidence: 99%